Step
*
2
1
1
of Lemma
name-comp_wf
1. I : Cname List
2. J : Cname List
3. K : Cname List
4. f : nameset(I) ⟶ extd-nameset(J)
5. ∀i,j:nameset(I).  ((↑isname(f i)) 
⇒ (↑isname(f j)) 
⇒ ((f i) = (f j) ∈ extd-nameset(J)) 
⇒ (i = j ∈ nameset(I)))
6. g : nameset(J) ⟶ extd-nameset(K)
7. ∀i,j:nameset(J).  ((↑isname(g i)) 
⇒ (↑isname(g j)) 
⇒ ((g i) = (g j) ∈ extd-nameset(K)) 
⇒ (i = j ∈ nameset(J)))
8. i : nameset(I)
9. j : nameset(I)
10. ↑isname(f i)
11. f i ∈ nameset(J)
12. ↑isname(f j)
13. f j ∈ nameset(J)
14. ↑isname(g (f i))
15. ↑isname(g (f j))
16. (g (f i)) = (g (f j)) ∈ extd-nameset(K)
⊢ i = j ∈ nameset(I)
BY
{ ((Assert (f i) = (f j) ∈ nameset(J) BY Auto) THEN Auto) }
Latex:
Latex:
1.  I  :  Cname  List
2.  J  :  Cname  List
3.  K  :  Cname  List
4.  f  :  nameset(I)  {}\mrightarrow{}  extd-nameset(J)
5.  \mforall{}i,j:nameset(I).    ((\muparrow{}isname(f  i))  {}\mRightarrow{}  (\muparrow{}isname(f  j))  {}\mRightarrow{}  ((f  i)  =  (f  j))  {}\mRightarrow{}  (i  =  j))
6.  g  :  nameset(J)  {}\mrightarrow{}  extd-nameset(K)
7.  \mforall{}i,j:nameset(J).    ((\muparrow{}isname(g  i))  {}\mRightarrow{}  (\muparrow{}isname(g  j))  {}\mRightarrow{}  ((g  i)  =  (g  j))  {}\mRightarrow{}  (i  =  j))
8.  i  :  nameset(I)
9.  j  :  nameset(I)
10.  \muparrow{}isname(f  i)
11.  f  i  \mmember{}  nameset(J)
12.  \muparrow{}isname(f  j)
13.  f  j  \mmember{}  nameset(J)
14.  \muparrow{}isname(g  (f  i))
15.  \muparrow{}isname(g  (f  j))
16.  (g  (f  i))  =  (g  (f  j))
\mvdash{}  i  =  j
By
Latex:
((Assert  (f  i)  =  (f  j)  BY  Auto)  THEN  Auto)
Home
Index